PENGARUH BOBOT TELUR TETAS ITIK TERHADAP PERKEMBANGAN EMBRIO, FERTILITAS DAN BOBOT TETAS - Paputungan, Sarini; Lambey, Lucia J.; Tangkau, Linda S.; Laihad, Jaqualine (Universitas Sam Ratulangi, 2017)
EFFECT OF DUCK EGG WEIGHT ON FERTILITY, EMBRYO DEVELOPMENT AND HATCHING WEIGHT OF DAY OLD DUCK. This study was done to evaluate embryonic development for determination of egg fertility and hatching weight of day old duck (DOD). This study involved 160 eggs of duck with the average egg weight (EW) classified into 55g ≤ EW < 60g, 61g ≤ EW < 65g, 65g ≤ EW < 70g and 71g ≤ EW < 75g. Data collection was conducted over 28 days, as long as the period of hatching process. The design method used in this study was completely randomized design. Existing data were analyzed using analysis of variance. Treatments in this study were 4 treatments and 4 replications at each treatment. The variables measured were the percentage of egg fertility, embryo development and hatching weight. Results showed that duck embryo development during the hatching process was in good condition process. The results of variance analysis showed that treatments of egg weight did not affect significantly the percentages of egg fertility. The percentages of fertility were ranging between 85 – 95%. Hatching weights were ranging between 31g – 51g per DOD. Based on the results of this study, it can be concluded that egg weight had no effect on the process of embryonic development and fertility, except those for the hatching weight of DOD. Key words: Duck egg weight, embryonic development, fertility, hatching weight.